Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/pssb.201046299
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of green InGaN laser on c‐plane GaN

Abstract: The challenges of green InGaN lasers are discussed concerning material quality as a function of InGaN composition, quantum well design and piezoelectrical fields. Investigations of polar quantum well designs and comparison with simulated nonpolar structures demonstrate that the quality of the indium rich layers is more important than the influence of interface charges. A high risk of dark spots at high In concentrations of 26-33% is observed. Small changes of about 2% of In significant reduce or increase the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 13 publications
0
30
1
Order By: Relevance
“…1(c). It is worth noting that also other authors reported that lasing from polar InGaN QWs is expected/observed when the electric field related to polarization effects is partially screened [14,32,33].…”
Section: Resultsmentioning
confidence: 71%
“…1(c). It is worth noting that also other authors reported that lasing from polar InGaN QWs is expected/observed when the electric field related to polarization effects is partially screened [14,32,33].…”
Section: Resultsmentioning
confidence: 71%
“…To accommodate the double bilayer structure of the wurtzite lattice along [0001], sites for only one sub-lattice on alternating bilayers are considered in the simulation (Fig. 2), this leads to a small offset in the simulation grids between the two types of bilayer along the [11][12][13][14][15][16][17][18][19][20] direction. The simulations were performed to deposit 1000 monolayers (MLs) of material onto the substrate, at rates of between 1 and 80 ML/s, and for both 400 x 400 and 800 x 800 site models with screw periodic boundary conditions.…”
Section: Modellingmentioning
confidence: 99%
“…Nucleation on the terrace of 2D islands without (c) and with (d) an ESB.Neighbors of atomic sites in the kinetic Monte Carlo simulations. The sub-lattices and six site neighbors for a site (larger circle) in each of the two bilayers, 1 and 2, are shown in red and physical sublattice is represented in the simulations, with a displacement of the hexagonal grid along ±[11][12][13][14][15][16][17][18][19][20] between each bilayer. flow growth mode without (a) and with (b) an ESB.…”
mentioning
confidence: 99%
“…A positive effect of built-in fields is however that it also reduces transition energy i.e. increases emission wavelength, which allows using less In concentration to achieve desired lasing wavelength [1]. But this benefit can only be useful if low optical gain is needed to reach threshold (Fig 1(a)), i.e.…”
mentioning
confidence: 97%
“…
During recent years, several research groups have demonstrated a steady progress in increasing InGaN quantum well (QW) laser emission wavelength [1][2][3][4][5], however the threshold current ( Fig. 1) and wall plug efficiency (WPE) are still worse than those for blue LDs.
…”
mentioning
confidence: 99%